Інноваційний розвиток як чинник конкурентоспроможності в умовах зовнішніх обмежень - Брюховецька, Н.Ю.; Коритько, Т.Ю. (Стратегія і механізми регулювання промислового розвитку, 2017)
Проаналізовано інноваційний розвиток України в контексті міжнародних індикаторів і рейтингів інноваційної діяльності. Виявлено основні проблеми підприємств в умовах євроінтеграції з ЄС. Проаналізовано індекс Європейського інноваційного табло і його вплив на конкуренто¬спроможність підприємств в умовах зовнішніх обмежень, обґрунтовано ключові напрями інноваційної політики. Анализируется инновационное развитие Украины в контексте международных индикаторов и рейтингов инновационной деятельности. Выявлены основные проблемы предприятий в условиях евроинтеграции в ЕС. Проанализирован индекс Европейского инновационного табло и его влияние на конкурентоспособность предприятий в условиях внешних ограничений, обоснованы ключевые направления инновационной политики. The activation of innovation activity at all levels of production is urgent for the Ukrainian economy. Effective development of the national economy depends mainly on the extent of implementation of the latest techniques and technologies. Enhancing innovation at all levels is important for the Ukrainian economy. Only innovative way of development through continuous updating equipment and technology, expansion of markets, effective use of scientific and technological capacity and stimulate its growth can ensure competitiveness of products and companies.
The level of innovation activity of enterprises is calculated as the ratio of innovation-active (employed by any type of innovation) companies to the total number companies in the country, sector, region, that been surveyed for a certain period of time.
The consolidated analysis of the achieved level and factors of the dynamics of Ukraine's innovation rating on global competitiveness indexes, the global innovation index and the European innovation scoreboard is presented. It is established that the feature of the Ukrainian innovation environment is, on the one hand, the presence of significant intellectual potential, and on the other hand, the lack of conditions for its full implementation.
The article is devoted to the place and role of the European innovation scoreboard in evaluating performance of scientific and technological potential of Ukraine and the EU.
Increased of domestic enterprises' innovation activity is one of the main prerequisites for stability and sustainable economic development. Business entities under uncertainty faced with factors that hinder the implementation of innovation, including: lack of own funds, significant costs of innovation, insufficient financial support from the state, rather high economic risk, long payback innovation.